Immunology of HPV-mediated cervical cancer: current understanding. (3rd September 2021) - Jee, Babban; Yadav, Renu; Pankaj, Sangeeta; Shahi, Shivendra Kumar
Abstract: Human papilloma virus (HPV) has emerged as a primary cause of cervical cancer worldwide. HPV is a relatively small (55 nm in diameter) and non-enveloped virus containing approximately 8 kb long double stranded circular DNA genome. To date, 228 genotypes of HPV have been identified. Although all HPV infections do not lead to the development of malignancy of cervix, only persistent infection of high-risk types of HPV (mainly with HPV16 and HPV18) results in the disease. In addition, the immunity of the patients also acts as a key determinant in the carcinogenesis. Since, no HPV type specific medication is available for the patient suffering with cervical cancer, hence, a deep understanding of the disease etiology may be vital for developing an effective strategy for its prevention and management. From the immunological perspectives, the entire mechanisms of disease progression still remain unclear despite continuous efforts. In the present review, the recent developments in immunology of HPV-mediated cervix carcinoma were discussed. At the end, the prevention of disease using HPV type specific recombinant vaccines was also highlighted.